Human extrahepatic and intrahepatic cholangiocyte organoids show region-specific differentiation potential and model cystic fibrosis-related bile duct disease - Monique M. A. Verstegen (Nature Portfolio, 2020)
Abstract The development, homeostasis, and repair of intrahepatic and extrahepatic bile ducts are thought to involve distinct mechanisms including proliferation and maturation of cholangiocyte and progenitor cells. This study aimed to characterize human extrahepatic cholangiocyte organoids (ECO) using canonical Wnt-stimulated culture medium previously developed for intrahepatic cholangiocyte organoids (ICO). Paired ECO and ICO were derived from common bile duct and liver tissue, respectively. Characterization showed both organoid types were highly similar, though some differences in size and gene expression were observed. Both ECO and ICO have cholangiocyte fate differentiation capacity. However, unlike ICO, ECO lack the potential for differentiation towards a hepatocyte-like fate. Importantly, ECO derived from a cystic fibrosis patient showed no CFTR channel activity but normal chloride channel and MDR1 transporter activity. In conclusion, this study shows that ECO and ICO have distinct lineage fate and that ECO provide a competent model to study extrahepatic bile duct diseases like cystic fibrosis.